Design and development of smart bicycle wall hanger - Muhammad Zulasyraf Bin Mohd Zainal (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
Common bicycle wall hanger design are difficult to operate, so a smart bicycle wall hanger is designed to reduce human effort in storing a bicycle and combine a few other functions from other products. The orientation of which least effort is used, along with the steps taken and energy required to store a bicycle will be measured. A static analysis was done to measure the amount of stress placed on the product. The method of product design and development used is a traditional staged process. In the end, the dimension required for the development of the smart bicycle wall hanger was obtained based on the concept design.